Algorithm to optimize thermodynamic parameters: A review (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Computational thermodynamics provides essential information for materials design. The CALPHAD (CALculation of PHAse Diagrams) method based on thermodynamic databases can be used for thermodynamic optimization and for calculating phase diagrams and thermodynamic properties in multicomponent systems. This article reviews the algorithms implemented in software for optimizing thermodynamic parameters. These software tools offer strong support for developing accurate thermodynamic databases. Recent advances in software and algorithms for thermodynamic parameter optimization are summarized, and their respective characteristics and potential limitations are analyzed. Finally, the development trends of software and algorithms for thermodynamic parameter optimization are discussed. This review will help interested readers understand the principles of thermodynamic optimization and contribute to the advancement of related algorithms.
Keywords: CALPHAD, Optimization methods, computational thermodynamic, database, Algorithm